INTELLECTUAL CAPITAL SEBAGAI DETERMINAN DALAM MENSTIMULUS BUSINESS PERFORMANCE (STUDI KASUS PADA PT. MAKASSAR MEGA PUTRA PRIMA) - Regina Afrianita (JURNAL PABEAN : PERPAJAKAN BISNIS EKONOMI AKUNTANSI MANAJEMEN, 2021)
This research is aimed to analyze intellectual capital as a determinant in stimulate the business performance of PT. Makassar Mega Putra Prima. The data used in this research is data obtained from the result of key interviews using qualitative descriptive analysis.The results of this study show that PT. Makassar Mega Putra Prima manages its intellectual capital well. The company considers intellectual capital to be a very valuable intangible asset. This can be seen from the management carried out by PT. Makassar Mega Putra Prima towards human capital, structural capital, and customer capital in supporting the company's business performance.